2019
DOI: 10.3390/w11122562
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Serious Games to Solve Water Problems: Editorial to the Special Issue on Game-Based Approaches to Sustainable Water Governance

Abstract: In this editorial, the authors (and guest editors) introduce the Special Issue titled Understanding Game-based Approaches for Improving Sustainable Water Governance: The Potential of Serious Games to Solve Water Problems. The authors take another look at the twelve contributions, starting from the subtitle question: what is the potential? The authors summarize the insights and give directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The use of educational videos and games has been demonstrated to improve understanding of the causes and impacts of marine issues. For example, Medema et al ( 2019 ) reported that many organisations concerned with sustainability and marine environments have begun to develop games with persuasive or learning messages, and that these games can prepare (and potentially incentivise) the changes urgently needed to address current and emerging environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…The use of educational videos and games has been demonstrated to improve understanding of the causes and impacts of marine issues. For example, Medema et al ( 2019 ) reported that many organisations concerned with sustainability and marine environments have begun to develop games with persuasive or learning messages, and that these games can prepare (and potentially incentivise) the changes urgently needed to address current and emerging environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…Serious games represent real-world issues and capture complexity while offering stakeholders greater freedom to think outside the box to explore different pathways for sustainability transformation (Gugerell and Zuidema 2017;Jean et al 2018). In light of this, they are increasingly being recognized within sustainability research and practice, as an approach to support the comprehension and improvement of wicked situations (Medema et al 2019). They can also be considered as an creative action learning approach that supports exploration and experimentation by harnessing diverse local knowledge and experience to determine appropriate actions (Rodela, Ligtenberg, and Bosma 2019;Salvini et al 2016).…”
Section: Systemic Practice: Serious Games and Co-designmentioning
confidence: 99%
“…Medema et al state that "water management and serious games are connected through complexity and social learning" [28]. Water management and decision-making, including drought planning, is "chaotic and messy" [29] because of the multitude of water uses and diverse stakeholder interests.…”
Section: Games and Drought Planningmentioning
confidence: 99%